Cyclophosphamide‐induced alterations of the micturition reflex in a novel in situ urinary bladder model in the anesthetized rat. Issue 4 (31st January 2014) - Aronsson, Patrik; Carlsson, Thomas; Winder, Michael; Tobin, Gunnar
<x xml:space="preserve">Abstract</x> Aims Cyclophosphamide‐induced cystitis alterations have been reported to occur both at efferent and afferent level in the micturition reflex arc. In particular, the stretching of the bladder wall causing urothelial release of ATP has been proposed as one of the pivotal mechanisms causing these alterations. To evaluate functional changes at efferent and afferent levels of the micturition reflex following cyclophosphamide treatment we have applied a novel in situ half bladder rat model. Methods Male Sprague‐Dawley rats were treated with either saline or cyclophosphamide (100 mg/kg), and stretch‐, electric‐, methacholine‐, and ATP‐induced responses were thereafter measured at 60–72 hr postinjection under pentobarbitone anesthesia. In the novel in situ half bladder model, the urinary bladder was prepared via a midline incision, where the two halves were separated all the way to the urethra as previously described. Results Following bladder stretch of 30–80 mN, of the half that was not used for tension measurement, the cyclophosphamide‐treated animals evoked significant two‐ to threefold larger contractile responses as compared to saline‐treated control animals. A sensitization of the afferent arm was shown in cyclophosphamide‐treated animals, since afferent stimulation evoked similar responses as in control animals despite that the efferent pelvic nerve stimulation displayed a lower contraction‐frequency relationship in cyclophosphamide‐treated animals. Atropine reduced the stretch(reflex)‐evoked contraction by up to 50% in control and 75–80% in cyclophosphamide‐treated rats. Subsequent addition of PPADS further reduced the contractions. Conclusion The micturition reflex response is increased following cyclophosphamide‐induced cystitis, as compared to control. The likely cause is sensitization at mechanosensor level in the micturition arc, which overrides the decrement of the efferent cholinergic effects. Neurourol. Urodynam. 34:375–380, 2015. © 2014 Wiley Periodicals, Inc.